Brain serotonergic activation in growth-stunted farmed salmon: adaption versus pathology. Issue 5 (May 2016) - Vindas, Marco A.; Johansen, Ida B.; Folkedal, Ole; Höglund, Erik; Gorissen, Marnix; Flik, Gert; Kristiansen, Tore S.; Øverli, Øyvind
Abstract : Signalling systems activated under stress are highly conserved, suggesting adaptive effects of their function. Pathologies arising from continued activation of such systems may represent a mismatch between evolutionary programming and current environments. Here, we use Atlantic salmon ( Salmo salar ) in aquaculture as a model to explore this stance of evolutionary-based medicine, for which empirical evidence has been lacking. Growth-stunted (GS) farmed fish were characterized by elevated brain serotonergic activation, increased cortisol production and behavioural inhibition. We make the novel observation that the serotonergic system in GS fish is unresponsive to additional stressors, yet a cortisol response is maintained. The inability of the serotonergic system to respond to additional stress, while a cortisol response is present, probably leads to both imbalance in energy metabolism and attenuated neural plasticity. Hence, we propose that serotonin-mediated behavioural inhibition may have evolved in vertebrates to minimize stress exposure in vulnerable individuals.